Effect of Peony (Paeonia ostii) Seed Meal Supplement on Enzyme Activities and Flavor Compounds of Chinese Traditional Soybean Paste during Fermentation - Weiqi Fu; Jiamin Ren; Shuwen Li; Dirong Ren; Xixi Li; Chenghuan Ren; Xueru Zhao; Jiaying Li; Fengjuan Li (Foods, 2023)
Peony seed meal (PSM) is the by-product obtained from peony seeds after oil extraction. In this study, PSM was incorporated into traditional koji-making, and its impacts on koji enzyme activities and flavor compounds in final products were investigated. In the process of koji fermentation, the optimal addition ratio of PSM to soybean was determined as 7:3. Under this ratio, the maximum enzyme activities of neutral protease, amylase, and glucoamylase were 1177.85, 686.58, and 1564.36 U/g, respectively, and the koji obtained was subjected to maturation. During post-fermentation, changes in the fermentation characteristics of the paste samples were monitored, and it was found that compared to the soybean paste without PSM, the enzyme activities maintained at a relatively good level. The PSM soybean paste contained a total of 80 flavor compounds and 11 key flavor compounds (OAV ≥ 1), including ethyl isovalerate, isovaleric acid, hexanal, phenylacetaldehyde, 3-Methyl-1-butanol 4-heptanone, 2-pentylfuran, methanethiol ester caproate, isoamyl acetate, 3-methyl-4-heptanone, and isovaleraldehyde. These findings could be used to improve the quality of traditional fermented paste, enrich its flavor, and simultaneously promote PSM as a valuable resource for fermented foods.